Compact Quantum‐Dot Microbeads with Sub‐Nanometer Emission Linewidth. (27th August 2021) - Kim, Kwon‐Hyeon; Dannenberg, Paul H.; Yan, Hao; Cho, Sangyeon; Yun, Seok‐Hyun
Abstract: Fluorescent microbeads are widely used for applications in life sciences and medical diagnosis. The spectral contrast and sharpness of photoluminescence are critical in the utilities of microbeads for imaging and multiplexing. Here, microbeads capable of generating single‐peak laser emission with a sub‐nanometer linewidth are demonstrated. The microbeads are made of quantum dots that are tightly packed and crosslinked via ligand exchange for high optical gain and refractive index as well as material stability. Bright single‐mode lasing with no photobleaching is achieved with particle diameters as small as 1.5 µm in the air. Sub‐nm lasing emission is maintained even inside high‐index surroundings, such as organic solvents and biological tissues. Feasibility of intracellular tagging and multi‐color imaging in vivo is demonstrated. Abstract : A single mode compact quantum‐dot microbead laser is demonstrated. This quantum dot (QD) microbead shows sub‐nanometer linewidth and excellent material stability. Ligand exchange with short bidentate ligands improves optical gain and refractive index, which as a result miniaturizes the size of laser down to 1.5 µm. Intracelluar tagging and multiplexed imaging in vivo are demonstrated with the QD microbeads.